Prevalence of Hard Ticks Infested Rabbits (Leporidae) Family in Iraq - Hadi, Afkar M. (Iraqi Journal of Science, 2025)
The present study aims to isolate and identify ectoparasites, specifically hard ticks, that infest both domestic and wild rabbits. This research is motivated by the heightened sensitivity of rabbits to infestations by hard ticks, which are recognized as the primary vectors of certain blood-borne diseases, particularly Viral Hemorrhagic Fever (VHF). The study areas were spread across five provinces in Iraq: Baghdad, Karbala, Wasit, Mosul, and Al-Anbar. A total of 85 hard ticks (42 male and 43 female) were infested by 57 rabbits (Leporidae Family), including 19 wild rabbits (hare) with an infestation rate of 100% and 38 domestic rabbits with an infestation rate of 18.42%. Total of infestation was 45.61%. The current results are the occurrence of two genera and five species of Ixodidae Family of hard ticks as follow: Hyalomma anatolicum (Koch, 1844) Rhipicephalus turanicus (Pomerantsef, 1946), Rhipicephalus leporis (Pomerantsef, 1946), Rhipicephalus pravus (Donitz, 1910) and Rhipicephalus appendiculatus (Neumann, 1901). Leporidae is considered the new host for the two species R. pravus and R. appendiculatus, as they previously recorded infested other domestic animals such as cattle and sheep in Iraq. Thus, this result contributes additional data to the understanding of hard tick biodiversity in Iraq.